Determinan Komplikasi Obstetri Di Indonesia (Analisis Data SDKI 2012) - seri laila (Politeknik Kementerian Kesehatan Banjarmasin, 2018)
Maternal mortality rate in Indonesia data IDHS on 2012 is still high at 359/100,000 live births, an increase of 57% compared to IDHS in 2007. One cause is due to obstetric complications. Compared to the 2002 and 2007 IDHS data, this figure is increasing and many factors affect the occurrence of obstetric complications. The objective is to know the determinant of obstetric complication based on IDHS data of 2012. This research use secondary data with cross sectional approach based on survey of IDHS 2012 with 4,618 samples. Result: Obstetric complication were 51,2% and there was significant correlation social of economy, parity, distance birth, history of complication, residence area, place of labor and quality of ANC to the obstetric complication. Result of research showed that there were correlation history of complication before OR=4,084, quality of ANC OR=1,187, place of labor OR=1,517, birth and parity spots interact with village residence against obstetric complications. Expected to improve quality services of ANC and ability of health worker to handle reference cases and improving readiness mother and family for recognize and anticipate incident of obstetric complication especially for mother who are at risk